The role of intraoperative frozen section in arthroplasty revision surgery: our experience - Di Benedetto, Paolo; Povegliano, Lorenzo; Cainero, Vanni; Gisonni, Renato; Beltrame, Alessandro; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: Due to the increasing the number of hip and knee replacement in the future will be increasing the number of cases of prosthetic revision. Our aim is to test the validity of extemporaneous exam for differentiation between septic and aseptic loosening of prosthetic. Methods: 159 patients underwent surgery for the prosthesis revision from 2008 to 2014 An intraoperative histological examination was performed during all the surgeries and multiple samples were taken for the conclusive histological examination and culture. Results: Sensitivity of the intraoperative histological examination resulted 38,3% (IC 0,26; 0,51); specificity 82,5% (IC 0,73; 0,90), where positive predictive value was 57,5% (IC 0,41; 0,73) and negative predictive value 68,4% (IC 0,59; 0,76). Conclusions: In the absence of a universally accepted method to diagnose infection in patients with mobilization of the prosthesis, intraoperative histological examination is, in spite of everything, a method easy to perform and reproduce, it shows high specificity and sensitivity in the presence of highly virulent pathogens.